An Analysis on Strategies in developing students’ soft-skills (A Case Study at a Bilingual School, Banda Aceh) - Emawati Emawati; Rahmantun Nisa; Teuku Zulfikar (Proceedings of AICS - Social Sciences, 2019)
The Indonesian educational system should guarantee that educational institutions in all levels not only train their students’ cognitive ability but also develop their affective domain. This important domain can be developed through various strategies, one of which is through shaping students’ soft-skills. This study was conducted to identify strategies implemented by a particular bilingual school in developing students’ soft-skills. Having interviewed four teachers and the school principal, observed classroom, and analyzed documents, we found that the teachers use various strategies in developing students’ soft-skills, one of which is through inviting students to participate in learning process and to engage in outdoor activities; promoting democratic dialogues; showing empathy and appreciation, and also showing good examples.